DEMOCRACIA E COMUNICAÇÃO ENTRE GOVERNO E POVO: O PRINCÍPIO DA IMPESSOALIDADE NA PRODUÇÃO DE PROPAGANDA DO GOVERNO - MARCOS ANTÔNIO STRIQUER SOARES (Universidade do Oeste Paulista, 2009)
This work examines the dangers of advertisement produced by government agencies to democracy. It investigates the totalitarianism advertisement produced in this type of political regime, especially in Nazi Germany; also, it investigates the populist and demagogic advertisement; it researches, finally, the failure of the disrespect to the impersonality principle in the production of public organisms, with addicts of selfpromotion, nepotism and partisanship. It considers that the Federal Constitution permits advertising of public organisms and that this is an indispensable tool for communication between rulers and ruled, in a globalized world, the rapid dissemination of information and diversity of sources. It notes, finally, that the advertisement of public organisms must undergo to strict control to avoid the degenerate use of this instrument of persuasion so powerful, and to prevent arbitrary decisions by government on duty and domination of the people.